“KORUPSI SEJARAH” DALAM ISLAM - Edi Susanto Edi Susanto (Institut Agama Islam Negeri Madura)
AbstractThis article tries to show that the internal conflicts among the ummah have broken since the early period of Islam. The critical study of early Islamic period to uncover the historical distortions was regarded dangerous and painful . A critical study of this early period will give us a new description of this period based on a strong data; and this critical history leads us to realize that such critical study will not violate the sacredness of Islam..Kata-kata kuncikorupsi sejarah, al-Khulafa’ al-Rasyidun, Dinasti Umayah, Dinasti Abbasiyah